Upaya Meningkatkan Kemampuan Memahami dan Menghafal Hukum Islam pada Pelajaran Fiqih Melalui Metode Mind Mapping di Madrasah Tsanawiyah Hidayatul Mubtadiin - Mufid Asrori; Dewiyanti Dewiyanti; Anita Anita (Journal on Education, 2024)
This research aims to improve the ability to understand and memorize Islamic law in fiqh lessons at Madrasah Tsanawiyah Hidayatul Mubtadiin through the application of the mind map method. Mind mapping is a visual technique that helps organize information systematically, making it easier for students to understand and remember the concepts being taught. This research uses an experimental method with subjects of class VIII students. Data was collected through comprehension and memorization tests before and after implementing the mind map, as well as through observation and interviews with students and teachers. The research results show that the use of the mind map method significantly increases students' ability to understand and memorize Islamic law. Students who were taught with mind maps showed an increase in comprehension and memorization test scores compared to before implementing this method. Apart from that, mind mapping also makes the learning process more interactive and interesting, thereby increasing students' learning motivation. Observations and interviews also revealed that students found it easier to memorize and remember information by using mind maps. Thus, the mind map method has proven to be effective in improving the quality of Islamic jurisprudence learning at Madrasah Tsanawiyah Hidayatul Mubtadiin. Applying this method not only helps students understand and memorize Islamic law better, but also develops their critical and creative thinking skills. Supporting factors such as the use of innovative learning methods, parental support, teacher training, and the availability of learning resources have contributed positively to this improvement. However, to achieve better results, it is still necessary to overcome inhibiting factors such as time constraints, lack of continuous teacher training, and low student motivation. Therefore, mind maps can be used as an innovative teaching strategy to improve student learning outcomes in fiqh subjects.